Answer:
x =
![(mn(q-p))/(n-m)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e842p9pmsh5lmgwg7geoqoiwnezo65qx0u.png)
Explanation:
collect the fractional terms on the left side of the equation and other terms on the right side
subtract
from both sides
-
+ p = q
subtract p from both sides
-
= q - p
We require the fractions to have a common denominator of mn
multiply the numerator/denominator of the first fraction by n and the numerator/denominator of the second fraction by m
-
= q - p
distribute and simplify the numerators of the fractions
= q - p
= q - p
factor out x from each term on the numerator
= q - p
multiply both sides by mn
x(n - m) = mn(q - p)
divide both sides by (n - m)
x =
→ n ≠ m